Richeza (c. 996-1063) – la reina consorte de Polonia – sabia o instigadora? - Anna Działak (Medievalista)
Richeza (b. ca. 996 – d. 1063) was the wife of Mieszko II Lambert – the second King of Poland and the granddaughter of Otto II – the Holy Roman Emperor. That educated woman, active both in the political arena and the arena of faith, did not enjoy, however, a merited acclaim in the chronicling of Middle Ages. What is more, the historiographic portrayal of that exceptional woman emerges as highly disfigured in the chronicles of medieval Poland and in the literature that followed. The objective of the current examination is to delve into analyzing that disfigurement and to depict its potential cause. It is also intended to juxtapose the figure of Richeza to other prodigious and prominent female figures representative of the circle of European culture. This is all in order to reconstruct the concealed cultural patterns.